Fiji sells live reef fish to Asian markets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Fiji is the first country in the South Pacific to export live reef fish to Asian countries. The live reef fishery programme is part of the commodity development framework programme of the Ministry of Agriculture; it is based in Bua province, on the...